Keabsahan Penjualan Tanah Objek Hak Tanggungan Oleh Debitur Tanpa Pemberitahuan Kepada Kreditur Pemegang Hak Tanggungan - Wafi, Muhammad Zaki Al; Putra, Mohamad Fajri Mekka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The activity of buying and selling land followed by the transfer of ownership assets to land is commonly carried out as a fulfillment of investment needs in the community. As with the existence of land which is an object of investment, land can be used to bring financial benefits through sales, rentals, or as collateral for debts and receivables. Land as collateral for debts and receivables held through a mortgage agreement gives birth to rights and obligations that must be fulfilled between the owner of the house as the debtor and the holder of the mortgage as the creditor. Even though it has been bound by a mortgage agreement, the existence of land that is still in the control of the debtor is often detrimental to the creditor, as is the case when the land is sold without the knowledge of the creditor. Legal research with this normative juridical research method will examine the validity of the sale and purchase agreement of the mortgage object by the debtor without being known by the creditor. Meanwhile, through this research, it will also examine the rights, obligations and responsibilities of the parties in a debt and credit agreement with a mortgage guarantee mechanism.